In vitro tissue culture: Towards conservation of threatened desiccation sensitive Encephalartos cycads seeds - Malwane, Thembeka Sebenzile Desiree (Department of Molecular and Cell Biology, 2020)
Approximately 62% of the 355 cycad species in the world are classified as threatened with extinction. The African genus, Encephalartos, has a total of 65 species, approximately 70% of which are threatened. This status emphasizes the need to conserve these species; however, the recalcitrant nature of cycads seeds makes it difficult to conserve using conventional seed banking methods. Recalcitrant seeds have a short lifespan and cannot be dried or stored for prolonged periods as they become non-viable when they lose moisture. While studies on cryopreservation for conserving cycad germplasm and banking these desiccation-sensitive seeds has made some advances, cycad conservation is still limited to ex situ living plant collections. In vitro tissue culture is a promising technique for conserving cycads. While attempts have been made, there have been few reported successes and, to date, there has been no successful regeneration of Encephalartos species. As such, this study was aimed at developing an efficient and successful in vitro regeneration protocol for two Encephalartos species. Embryo regeneration of E. altensteinii and E. manikensis was assessed, testing the effects of plant growth regulators (PGRs) - 0.5 mg/L Kinetin and 0.5 mg/L 6-BAP, alone or in combination, sucrose (0, 15 and 30 g/L) and light. Within six weeks of culture, embryos of both species were able to regenerate, however, each responded differently to the tested variables. While shoot regeneration was evident for both species during this period, this was however not explained by any of the variables assessed in this study. Rooting was highest in the treatments with 0.5 mg/L Kinetin for E. altensteinii, after subculture rooting was favoured by the treatments with 0.5 mg/L Kinetin + 0.5 mg/L 6-BAP. Encephalartos manikensis rooting was significantly higher in PGR-free treatment in the first six weeks of culture. After subculture, rooting was enhanced by the treatment with the highest PGR concentration of 1.0 mg/L Kinetin + 1.0 mg/L 6-BAP. Darkness enhanced rooting while 16h photoperiod enhanced shooting for both species. However, the regeneration of both roots and shoots was more prevalent in the treatments that were initiated in complete darkness as compared to the treatments initiated under 24h of light. Both species responded to sucrose; with increase in sucrose concentration, callus induction increased for E. altensteinii while, necrosis and contamination increased for E. manikensis. In vitro-derived E. altensteinii plantlets acclimatization was unsuccessful and only 3.5% of E. manikensis were successfully acclimatized. This study suggests that although both these species belong to the same genus, in vitro culture protocol should be species specific. The overall regeneration of both species was however low, thus the second study assessed the levels of phytohormones in E. altensteinii seed tissues (embryos and megagametophytes) of the same age as those used in the in vitro regeneration. Phytohormones, as well as multiple phytohormone interactions (i.e. interplay between Abscisic acid (ABA) and Gibberellins (GAs)), play a role in the germination, growth and development of a plant. The high levels of a germination inhibiting ABA compared to the low levels of cytokinins and auxins, as well as the absence of GAs obtained in the assessed seed tissue, suggest that no real germination was taking place. Thus these results suggest that E. altensteinii seeds have a very slow developmental process with the likely chance that at this age they may be immature.